Anti-obesity public service announcements : an exploratory study on perceived realism and identification with advertisement characters = Anuncios públicos contra la obesidad : estudio exploratorio sobre realismo percibido e identificación con los personajes de anuncios - Wrzecionkowska, Dagmara
Mass media outreach represents an important vehicle to address widespread obesity; however, literature evaluating the effectiveness of the anti-obesity message is scarce, and the concept of identification has not been reviewed in that context. Identification with message characters and perception of realism facilitate engagement and foster message effectiveness. Fifteen women were presented with four portrayals of the overweight, in one-on-one interviews: (1) a sedentary, overeating obese individual; (2) an overweight person struggling with daily activities; (3) another overweight person in a low-income socio-economic context, and (4) an overweight woman exercising and limiting her in portions. This exploratory study indicates that associating an obese person with some negatively perceived activities limits identification, regardless of activities being perceived as realistic.